Paleolimnological evidence of environmental changes in seven subtropical reservoirs based on metals, nutrients, and sedimentation rates - Cardoso-Silva, Sheila; Oliveira Soares Silva Mizael, Juliana [UNESP]; Frascareli, Daniele [UNESP]; Alves de Lima Ferreira, Paulo; Henrique Rosa, André [UNESP]; Vicente, Eduardo; César Lopes Figueira, Rubens; L. M. Pompêo, Marcelo; Moschini-Carlos, Viviane [UNESP] (Elsevier, 2021)
Paleolimnological research can shed light on a broad range of environmental concerns; however, such studies are scarce in reservoirs. To address this lack of knowledge, a paleolimnological investigation was conducted to determine historical changes in sedimentation rates (SR), using 210Pb geochronology, and concentrations of nutrients and metals (Cr, Cu, Ni, Pb, Zn, Al, Mn, Fe) in seven subtropical reservoirs (São Paulo, Brazil). Sediment cores were collected in the dam areas. Increasing SR was observed in all reservoirs and was mainly attributed to eutrophication and changes in land use and occupation. Considering the total nitrogen and/or phosphorus, the sediment could be considered polluted at the Broa, Barra Bonita, Salto Grande, and Rio Grande reservoirs. Decreasing values were observed for Pb when the use of tetraethyl lead as an additive in gasoline was forbidden (1990). According to the applied indices, no significant enrichment, contamination, or ecological risk for metals were registered, except at the Rio Grande reservoir. At this reservoir, a moderate enrichment of Mn was observed since 1999, which was mainly associated with municipal wastewater and erosive processes, as indicated by a significant correlation between Mn and SR (r = 0.73, p < 0.0001). A very high enrichment of Cu was observed. The accumulation of Cu in this reservoir peaked in 2006 to 6183.0 mgCu/kg, a value 412-fold higher than the background. Even during a period before intense industrialisation, concentrations of Cu were 49-fold higher than background levels. The increase of Cu in bottom sediments could be attributed to vertical migration according to a series of complex mechanisms; however, further research will be needed to improve the understanding of Cu dynamics. This work makes an important contribution to understanding the paleolimnology of reservoirs, and the findings could also be applied in other contexts, since the impact of metal contamination in water bodies is a global-scale problem.
Keywords: Background levels; Contamination; Copper; Ecological Risk; Metal Migration